Barriers in the Julian Alps and Notitia Dignitatum - Kos, Peter (Arheološki vestnik, 2013)
The author analyses the description and depiction of the function of the comes Italiae in the manual Notitia Dignitatum from the beginning of the 5th century, and establishes that the term tractus Italiae circa Alpes cannot be understood to mean the entire Alpine belt from the Ligurian Sea to the Bay of Kvarner. The argument is also presented that the expression refers only to the line of barrier walls with towers in the Julian Alps from the 4th century, for which the term from Ammianus Marcellinus is also used, i.e. claustra Alpium Iuliarum. The expression need not refer to the system of defence-in-depth that was placed after the cease in activity of the linear barriers at the beginning of the 5th century. The three legions of the Iuliae Alpinae mentioned by the Notitia Dignitatum, which must be related to the Julian Alps because of this name, cannot be connected to the function of comes Italiae